Amphibious vision – Optical design model of the hooded merganser eye. (October 2020) - Urban, Ilka; Uwurukundo, Xavier; Stumpf, Daniela; Frey, Katharina; Reichenbach, Andreas; Francke, Mike; Brüning, Robert; Brunner, Robert
Highlights: Schematic eye model of the hooded merganser. Verification of the accommodation mechanism of amphibious animals. Comparison of the visual abilities of the hooded merganser eye in air and water. Abstract: A comprehensive schematic eye model of the hooded merganser is introduced for the first time to advance the understanding of amphibious vision. It is comprised of two different configurations, the first one modeling its visual system in air (unaccommodated state) and the second one representing the case where the eye is immersed in water (accommodated state). The model was designed using available data of former studies, image analysis and the implementation of feasible assumptions that serve as starting values. An optimization process incorporating an optical design program is used to vary the starting values with the aim of finding the setup offering the best acuity. The image quality was measured using the root-mean-square radius of the focal spot formed on the retina. The resulting schematic eye model comprises all relevant optical specifications, including aspherical geometrical parameters for cornea and lens, distances between the surfaces, the gradient index distribution of the lens, the retinal specifications and the object distance in both media. It achieves a spot radius of 4.20 μ m for the unaccommodated state, which meets the expectations derived by the mean ganglion cell density and comparison with other animals. In contrast, under water the determined spot radius of 11.48 µ m indicates an acuity loss. As well as enhancing our understanding of the vision of the hooded merganser, the schematic eye model may also serve as a simulation basis for examing similar animal eyes, such as the cormorant or other fish hunting birds.